Constraint programing for solving four complex flexible shop scheduling problems. Issue 2 (21st February 2021) - Meng, Leilei; Lu, Chao; Zhang, Biao; Ren, Yaping; Lv, Chang; Sang, Hongyan; Li, Junqing; Zhang, Chaoyong
Abstract: In recent years, with the advent of robust solvers such as Cplex and Gurobi, constraint programing (CP) has been widely applied to a variety of scheduling problems. This paper presents CP models for formulating four scheduling problems with minimal makespan and complex constraints: the no‐wait hybrid flow shop scheduling problem, the hybrid flow shop scheduling problem with sequence‐dependent setup times, the flexible job shop scheduling problem with worker flexibility and the semiconductor final testing problem. The advantages of CP method in solving these four complex scheduling problems are explored. Finally, a set of benchmark instances are adopted to demonstrate the effectiveness and efficiency of the CP method. Experiment results show that the proposed CP models outperform existing algorithms; in particular, several best‐known solutions of benchmark instances are improved by our CP method.